PROFILE OF A MODERN RESEARCHER IN SOCIAL NETWORKS (Innovative professional education, 2022)
The services of information and digital systems, which are now widely used to evaluate the effectiveness of the activities of scientific and scientific-pedagogical workers, divisions of higher education institutions and scientific institutions, are characterized. Attention is focused on presenting the profile of a scientific and scientific-pedagogical worker in social networks. The peculiarities of their use for the development of a scientific career are substantiated.
Keywords: research profile, social networks, scientific, scientific and pedagogical activity, digital competence of the researcher